2022
DOI: 10.1002/jhbp.1287
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid profiles in choledocholithiasis and their ability to predict common bile duct stone recurrence after endoscopic retrograde cholangiopancreatography treatment

Abstract: Background/Purpose This study aimed to explore the alteration of bile acid (BA) profiles in patients with choledocholithiasis (CDC) and construct a prediction model for evaluating the risk of common bile duct stone (CBDS) recurrence after endoscopic treatment. Methods A total of 320 patients (218 with CDC and 102 with nonneoplastic polyps) were enrolled. The serum BA profiles were compared between groups. Both diagnostic score of CDC and prognostic risk score of CBDS recurrence based on BAs were established by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Overall, 35 studies ( n = 11,771) reported the recurrence of CBD stones after initial clearance with ERCP 1–6,11–27,29–41 . The pooled event rate for the recurrence of CBD stones was 12.6% (95% confidence interval [CI]: 11.2–13.9; I 2 = 79.2%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 35 studies ( n = 11,771) reported the recurrence of CBD stones after initial clearance with ERCP 1–6,11–27,29–41 . The pooled event rate for the recurrence of CBD stones was 12.6% (95% confidence interval [CI]: 11.2–13.9; I 2 = 79.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the PRISMA diagram for the study selection and inclusion process. A total of 37 studies with 12,952 patients were included in the final analysis 1–6,11–41 . Table 1 shows the baseline characteristics of the studies included in the present meta‐analysis, along with the study quality assessment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations